Health Inequalities through the Lens of Health Capital Theory: Issues, Solutions, and Future Directions - Titus J. Galama; Hans van Kippersluis (Tinbergen Institute, 2013)
We explore what health-capital theory has to offer in terms of informing and directing research into health inequality. We argue that economic theory can help in identifying mechanisms through which specific socioeconomic indicators and health interact. Our reading of the literature, and our own work, leads us to conclude that non-degenerate versions of the Grossman model (1972a;b) and its extensions can explain many salient stylized facts on health inequalities. Yet, further development is required in at least two directions. First, a childhood phase needs to be incorporated, in recognition of the importance of childhood endowments and investments in the determination of later-life socioeconomic and health outcomes. Second, a unified theory of joint investment in skill (or human) capital and in health capital could provide a basis for a theory of the relationship between education and health.
Keywords: I12; I14; 330; Health Capital Models; Health Inequality; Gesundheit; Soziale Ungleichheit; Sozialer Indikator; Gesundheitsökonomik